2010
DOI: 10.1176/appi.psy.51.3.248
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Interleukin-10 and Tumor Necrosis Factor Are Both Associated With Vital Exhaustion in Patients With Cardiovascular Risk Factors

Abstract: The subjective state of vital exhaustion is linked to a substantial alteration in the pattern of secreted cytokines. Data suggest that a disturbance in the levels of both pro-inflammatory and anti-inflammatory mediators, rather than isolated stimulation by pro-inflammatory cytokines, is associated with the mental and physical changes of vital exhaustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
7

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
11
0
7
Order By: Relevance
“…We anticipated finding a correlation between elevated TNF-α values and reduced muscle strength in the present study since TNF-α has been linked to muscle loss and increased fatigue in heart failure patients (Anker & Sharma, 2002; Meyer et al, 2010). Our data did not support this hypothesis.…”
Section: Discussionmentioning
confidence: 86%
“…We anticipated finding a correlation between elevated TNF-α values and reduced muscle strength in the present study since TNF-α has been linked to muscle loss and increased fatigue in heart failure patients (Anker & Sharma, 2002; Meyer et al, 2010). Our data did not support this hypothesis.…”
Section: Discussionmentioning
confidence: 86%
“…35 Previous studies reported divergent findings. 4,5,18 For example, van der Ven et al 5 and Appels et al 18 observed moderately large mean differences between exhausted and non-exhausted patients for IL-6 5,18 and IL-10, 5 suggesting that elevated IL-6 and IL-10 may mediate or contribute to exhaustion and low-grade chronic inflammation that characterizes coronary atherosclerosis. The fate of post-CABG exhaustion may be linked to disruption in the balanced expression of pro- and anti-inflammation as purported by mechanisms underlying atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, exhaustion was associated with elevated levels of IL-10 in adults with cardiovascular risk factors for heart failure. 4 Furthermore, elevated baseline IL-6 and IL-10 increased the risk of late cardiac events among exhausted post-percutaneous coronary intervention patients. 3 Elevated IL-10 in exhaustion may suggest the presence of heightened systemic inflammation, whereas deficiency of IL-10 may suggest the existence of a persistent inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…B. Tumornekrosefaktor alpha (TNF-α) und Interleukin (IL) 6 führen [15]. Bei Patienten mit Herzinsuffizienzrisikofaktoren konnten wir kürzlich zeigen, dass das mit der Depression verwandte Gefühl der "vitalen Erschöpfung" positiv sowohl mit dem proinflammatorischen TNF-α als auch mit dem antiinflammatorischen IL-10 assoziiert war [16]. Zumindest die proinflammatorischen Zytokine können ihrerseits Symptome wie Schwä-che-und Krankheitsgefühl oder Abgeschlagenheit hervorrufen (sog.…”
Section: Inflammatorische Prozesse Als Mediatoren Zwischen Herz Und Punclassified